'Papists' and prejudice : popular anti-Catholicism and Anglo-Irish conflict in the north east of England, 1845-70 /: popular anti-Catholicism and Anglo-Irish conflict in the north east of England, 1845-70. (2013) - Bush, Jonathan
No abstract available